Pengaruh Cita Rasa Dan Kualitas Pelayanan Terhadap Minat Beli Pada Rumah Makan Bebek Senjay Bumbu Hitam “Cak Rizky” Kasihan UMY (Cabang Seturan Yogyakarta) - Abdul Rozak; Kristiana Sri Utami (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The author will conduct research entitled "The Effect Of Taste And Service Quality On Buying Interest At The Black Bumbu Bebek Senjay Food House "Cak Rizky" Kasihan UMY (Seturan Branch Yogyakarta)" The research taken is using quantitative research. The research taken is information related to taste, service quality to consumer buying interest. This research is a causal relationship (Causal Explanatory) which proves the usual relationship. Taste, service quality is called the independent variable, buying interest is called the dependent variable. In this study the population is not limited, so the sampling uses 100 respondents. 1. Taste has a significance value of 0.008 0.05, these results indicate that the Taste variable has a positive and significant effect on Buying Interest in the black spice senjay duck restaurant "Cak Rizky" Kasihan UMY 2. Service Quality has a significance value of 0.000 0, 05, these results indicate that the Service Quality variable has a positive and significant effect on Buying Interest in the black spice senjay duck restaurant "Cak Rizky" Kasihan UMY 3. Taste and Service Quality have a significance of 0.000 0.05, these results indicate that the variables of Taste and Service Quality have a significant effect simultaneously on Buying Interest in the black spice senjay duck restaurant "Cak Rizky" Kasihan UMY.